2022
DOI: 10.1111/cdoe.12747
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of socioeconomic inequalities in the prevalence of untreated dental caries in early childhood: Results from three birth cohorts in southern Brazil

Abstract: Objectives To estimate the socioeconomic disparities in untreated dental caries in early childhood according to socioeconomic characteristics in three birth cohorts in Southern Brazil. Methods The socioeconomic data to this study were collected at the 48‐month follow‐up and oral health studies of 1993, 2004 and 2015 Pelotas birth cohort studies. The outcome was untreated dental caries in children aged 6 (1993 cohort), 5 (2004 cohort) and 4 years (2015 cohort), dichotomized into absence/presence. Analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…But poor oral health status was explained strongly and consistently by structural determinants more than by intermediate determinants. Similar studies concluded that the former are better at explaining the health differences between individuals than the latter [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Do [3] explained that the differences between oral health status are best illustrated by countries' social and macro-economic policies, while the differences within a country are defined by socioeconomic position like the Chilean situation from our findings.…”
Section: Candy Consumptionsupporting
confidence: 71%
See 1 more Smart Citation
“…But poor oral health status was explained strongly and consistently by structural determinants more than by intermediate determinants. Similar studies concluded that the former are better at explaining the health differences between individuals than the latter [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Do [3] explained that the differences between oral health status are best illustrated by countries' social and macro-economic policies, while the differences within a country are defined by socioeconomic position like the Chilean situation from our findings.…”
Section: Candy Consumptionsupporting
confidence: 71%
“…Despite the fact that Social Determinants of Health (SDH) studies in Latin-American children are more limited, some reports have suggested that oral health differences are strongly associated with family socioeconomic level, caregivers' educational level, family income and access to fluoridated water [15][16][17][18]. However, the evidence is not yet conclusive, since most studies analyze the structural and intermediate social determinants separately and there are relevant differences between economic development and culture between countries in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Among children, dental caries is the most prevalent chronic condition, affecting 60-90% of children globally [11]. For children in low-and middle-income countries (LMIC), and low-income populations in high-income countries, the high prevalence of dental caries and limited access to dental care has left much tooth decay untreated [12][13][14]. Untreated caries can contribute to a poorer quality of life, malnutrition, daily performance, and difficulty sleeping and eating due to mouth pain [4,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only fragmentary knowledge exists about the correlation to factors such as wealth inequality within a nation index 13,14 (Gini coe cient) and/or gross national income per capita/year (GNI) of several countries. The numbers of ECC do not fall as rapidly as anticipated especially among socioeconomically deprived children 15 , therefore, it is critical to investigate the association between background social and economic factors and ECC prevalence/experience worldwide. Starting from these premises, this systematic review and meta-analysis were aimed to synthesize existing research ndings regarding ECC prevalence and experience globally over the last ten years and to describe its distribution by country as well as its links to various socio-economic indicators.…”
Section: Introductionmentioning
confidence: 99%